Association between screen time and dry eye symptoms - Janeth Angelica Jansen; Cisca Kuswidyati; Febie Chriestya (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Electronic media has become a necessity in everyday life because of its function to access information, communication, etc. These functions cause an increase in average screen time and risk of developing dry eye symptoms such as photophobia, grittiness, sore eyes, and blurred vision.Objective: This study aims to determine whether there is a relationship between screen time and dry eye symptoms.Methods: An observational-analytic study with a cross-sectional approach was conducted on 66 medical students. All students would download a screen time application on each electronic media they have for one week before data collection. Furthermore, data were collected using a questionnaire consisted of screen time and Ocular Surface Disease Index (OSDI) and were statistically analyzed.Results: A total of 90.91% of the students use electronic media =8 hours/day. The proportion of students who experience dry eye symptoms is 46.97%. There was no statistically significant between screen time and dry eye symptoms (p = 0.676).Conclusion: More than ninety percent of students spend more than 8 hours/day using electronic media but no statistically significant between screen time and dry eye (p>0.05).